Risk Analyses Factor of Infant Mortality Caused by Tetanus Neonatorum in East Java - Selvy Novita Sari (Universitas Airlangga, 2017)
Tetanus neonatorum is an infection in infants ( < 28 days), caused by bacteria Clostridium tetani that enter the body through the wound. Tetanus neonatorum is one of the leading causes of neonatal mortality in the world. The case of tetanus neonatorum is present in 14 provinces in Indonesia, East Java has the second highest case of tetanus neonatorum. Factors affecting infant mortality among others include maternal immunization status, parity, delay admission of TN patients, and umbilical cord care. The purpose of this study was to analyze the relationship between maternal immunization status, parity, delay admission of TN patients, and umbilical cord care with mortality of tetanus neonatorum. This study uses cross sectional design using 59 respondents obtained from T2 report to Dinas Kesehatan Provinsi Jawa Timur in 2014-2016. The result of the research by using chi-square test and α= 0,05 obtained TT immunization of pregnant women (p = 0.257), parity (p = 0.034; PR= 0.39; 95% CI 0.16-0.98), delay admission of TN patients (p = 0.061), and umbilical cord care (p = 0.007; PR = 2.31; 95% CI 1.29-4.15). The conclusion of this study is there are no relationships between maternal immunization status and delay admission with mortality of tetanus neonatorum and a significant relationships between parity and umbilical cord care with mortality of tetanus neonatorum in East Java in 2014-2016. To reduce the risk factors of infant mortality, it is necessary to socialize TT immunization to pregnant women, planning of pregnancy, clean delivery and umbilical cord care. Keywords: risk factors, delay admission, mortality of tetanus neonatorum, parity, and umbilical cord care, maternal immunization